ChemInform Abstract: Suzuki—Miyaura Coupling of Aryl Chlorides with Arylboronic Acids Using the Morpholine—NiCl2 Catalyst System. Issue 15 (April 2015) - Abe, Taichi; Mino, Takashi; Watanabe, Kohei; Sakamoto, Masami
Abstract: The coupling of aryl chlorides succeeds with aryl and hetaryl boronic acids and even alkenyl boronic acids, but fails for alkyl boronic acids.